STRATEGI PENGEMBANGAN HUTAN KEMASYARAKATAN DENGAN POLA AGROFORESTRY DI DESA RANA KOLONG KECAMATAN KOTA KOMBA KABUPATEN MANGGARAI TIMUR - Diaz, Renalthy Lidwina; Seran, Wilhelmina; Riwu Kaho, Norman P.L.B. (Wana Lestari, 2022)
Forest is a stretch of land with a certain area that is overgrown with trees and other plants. Forests have functions as production forests, conservation forests and protection forests. Through the Ministry of Environment and Forestry held a Social Forestry program to improve the welfare of communities around the forest through a pattern of empowerment and remain guided by aspects of forest sustainability and in the form of Village Forests, Community Forests, Community Plantation Forests, Customary Forests and Partnership Forest. Communty Forests activities are only applied in protected forest areas and production forests. The purpose of the study was to determine the Communty Forests development strategy and agroforestry pattern in Rana Kolong Village, Komba City District, East Manggarai Regency which was carried out for 3 months from August - October 2020. The Communty Forests development strategy with agroforestry patterns in Rana Kolong village was formulated using SWOT analysis. SWOT analysis is a strategic planning method to evaluate the factors that influence efforts to achieve goals, namely comparing strengths, weaknesses, opportunities and threats. The level of community dependence on forests is very high, as evidenced by the large number of people who have arable land in forest areas with cultivation of Cloves (Syzygium aromaticum), Avocado (Persea americana), Candlenut (Aleurites moluccanus), Cocoa (Theobroma cacao), Coconut (Cocous nucifera). , Areca nut (Areca cetechu), Aren (Arenga pinnata), Bamboo (Bambuseae), Coffee (Coffea), Sweet Potato (Ipomoea batatas), Cassava (Manihot esculenta), Porang (Amorphopallus muelleri), White Teak (Gmelina arborea), Sengon (Albizia chinensis) and Mahogany (Swietenia mahagoni). The results showed that the strategy recommendation obtained to improve the Communty Forests development strategy with an agroforestry pattern in the research area was the SO (Strenghts-Opportunities) strategy, namely by using opportunities to take advantage of existing strengths with activities such as increasing community participation in managing and supporting the utilization of Communty Forests with a pattern. agroforestry, increasing the government's role in the development of local and non-local plants, compiling a management plan for the use of Communty Forests areas to develop wood and non-timber plant species in accordance with Communty Forests land conditions, seeing legal support on Communty Forests as a reference material.